Serum Procalcitonin in Diabetes Mellitus with and Without Pulmonary Tuberculosis - Eka Fitriana; James P. Simanjuntak; Herry Hermansyah; Karnelli Karnelli (Journal of Community Health Provision, 2026)
Diabetes mellitus (DM) is associated with immune dysfunction and increased susceptibility to pulmonary tuberculosis (TB). Procalcitonin (PCT) is widely used as a biomarker of bacterial infection, but its concentrations in patients with DM and pulmonary TB remain insufficiently characterized. To compare serum PCT concentrations between patients with DM with and without active pulmonary TB. This analytical cross-sectional study included 50 patients with DM recruited from two primary healthcare centers in Jambi, Indonesia, from March to June 2025. Participants comprised 34 patients without pulmonary TB and 16 with active pulmonary TB. Serum PCT was measured using fluorescence immunoassay. Non-normally distributed PCT concentrations were summarized using the median and interquartile range (IQR) and compared using the Mann–Whitney U test.PCT concentrations were within the normal reference range (